Critical role of C5a in sickle cell disease. Issue 3 (3rd January 2019) - Vercellotti, Gregory M.; Dalmasso, Agustin P.; Schaid, Terry R.; Nguyen, Julia; Chen, Chunsheng; Ericson, Marna E.; Abdulla, Fuad; Killeen, Trevor; Lindorfer, Margaret A.; Taylor, Ronald P.; Belcher, John D.
Abstract : Innate immune complement activation may contribute to sickle cell disease (SCD) pathogenesis. Ischemia‐reperfusion physiology is a key component of the inflammatory and vaso‐occlusive milieu in SCD and is associated with complement activation. C5a is an anaphylatoxin, a potent pro‐inflammatory mediator that can activate leukocytes, platelets, and endothelial cells, all of which play a role in vaso‐occlusion. We hypothesize that hypoxia‐reoxygenation (H/R) in SCD mice activates complement, promoting inflammation and vaso‐occlusion. At baseline and after H/R, sickle Townes‐SS mice had increased C3 activation fragments and C5b‐9 deposition in kidneys, livers and lungs and alternative pathway Bb fragments in plasma compared to control AA‐mice. Activated complement promoted vaso‐occlusion (microvascular stasis) in SS‐mice; infusion of zymosan‐activated, but not heat‐inactivated serum, induced substantial vaso‐occlusion in the skin venules of SS‐mice. Infusion of recombinant C5a induced stasis in SS, but not AA‐mice that was blocked by anti‐C5a receptor (C5aR) IgG. C5a‐mediated stasis was accompanied by inflammatory responses in SS‐mice including NF‐κB activation and increased expression of TLR4 and adhesion molecules VCAM‐1, ICAM‐1, and E‐selectin in the liver. Anti‐C5aR IgG blocked these inflammatory responses. Also, C5a rapidly up‐regulated Weibel‐Palade body P‐selectin and von Willebrand factor on the surface of human umbilical vein endothelial cells in vitro and on vascular endothelium in vivo. In SS‐mice, a blocking antibody to P‐selectin inhibited C5a‐induced stasis. Similarly, an antibody to C5 that blocks murine C5 cleavage or an antibody that blocks C5aR inhibited H/R‐induced stasis in SS‐mice. These results suggest that inhibition of C5a may be beneficial in SCD.